2016
DOI: 10.1016/j.vaccine.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Provider communication and HPV vaccination: The impact of recommendation quality

Abstract: Background Receiving a healthcare provider’s recommendation is a strong predictor of HPV vaccination, but little is known empirically about which types of recommendation are most influential. Thus, we sought to investigate the relationship between recommendation quality and HPV vaccination among U.S. adolescents. Methods In 2014, we conducted a national, online survey of 1,495 parents of 11- to 17-year-old adolescents. Parents reported whether providers endorsed HPV vaccination strongly, encouraged same-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
277
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 334 publications
(311 citation statements)
references
References 22 publications
(34 reference statements)
20
277
1
4
Order By: Relevance
“…52,63 Provider communication was consistently associated with patients' sex such that providers' recommendation intentions and behavior were more supportive of HPV vaccination for girls versus boys. 10,12,24,25,29,33,37,44,55,57,58,60,64,65 For example, the 2014 NIS-Teen found that 64% of age-eligible girls had received a provider recommendation compared to just 42% of boys. 10 All but one study examining patients' race/ethnicity suggested disparities in provider communication with parents of African American and Hispanic adolescents less often discussing HPV vaccine with a provider or receiving HPV recommendations than parents of non-Hispanic White adolescents.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 4 more Smart Citations
“…52,63 Provider communication was consistently associated with patients' sex such that providers' recommendation intentions and behavior were more supportive of HPV vaccination for girls versus boys. 10,12,24,25,29,33,37,44,55,57,58,60,64,65 For example, the 2014 NIS-Teen found that 64% of age-eligible girls had received a provider recommendation compared to just 42% of boys. 10 All but one study examining patients' race/ethnicity suggested disparities in provider communication with parents of African American and Hispanic adolescents less often discussing HPV vaccine with a provider or receiving HPV recommendations than parents of non-Hispanic White adolescents.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…Some studies emphasized their lack of participation, particularly in the case of younger adolescents. 4,19,74,78,79 Indeed, some parents indicated a preference for vaccinating in the preteen years specifically because they viewed adolescents as having little say during this 11 Cross-sectional, online survey rout rout F, M 776 National sample of pediatricians and family physicians Gilkey, 2016 60 Cross-sectional, online survey rout rout F, M 1495 National sample of parents of adolescents (ages 11-17) Gilkey, under review 16 Cross-sectional, online survey rout rout F, M 1484 National sample of parents of adolescents (ages [11][12][13][14][15][16][17] (Continued on next page) time. 18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege.…”
Section: Communication Rolesmentioning
confidence: 99%
See 3 more Smart Citations